Strategic evaluation of Quezon City Library and Information Center CaféLIB - Razal, Johannah Mae O.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study was conducted to evaluate Café@Lib of the Quezon City Public Library using three complementary methods. These methods are SWOT analysis, environmental scanning and three of Michael Porters' 5 forces analysis - threat of new entrant, threat of substitute product and services, and rivalry among existing competitors.
Interview and questionnaire served as the main instruments in the study. Observations, ocular visits, and literature research were used as supplemental instruments to support the study. Fifty three (53) Quezon City Library and Information Center: Café@Lib users, 25 people within 500 meters vicinity radius of QCLIC, and the librarian of QCLIC were the respondents of the study.
The research findings identified the strengths, weaknesses, opportunities and threats of Café@Lib using SWOT analysis. Café@Lib strengths are the collection is interesting and up-to-date, has a standard classification system, an inviting ambience, an accommodating staff, with variety of food choices, and loyal customers. The weakness was focused on the marketing of Café@Lib, competence of staff, improvements of some facilities and unmanaged noise. It offers an opportunity to market the library collection and services in a comfortable way as library café is a new experience in Philippine Public library.
The factors that can affect the Café@Lib in the future are the possible entry of new competitors, marketing of Café@Lib, change of preference of the users, number of users and staff. The products that can serve as substitute to the products of Café@Lib are milk tea, milkshake, fruit juice and doughnuts. The threat of new entrant of Library café near the vicinity of Quezon City Public Library and Information Center is low and there is no threat of new competitor.
Results of the study revealed that Quezon City Library and Information Center: Café@Lib is performing well. Café@Lib is well managed with some flaws to improve. Recommendations formulated were based on the needs of the users, the organization and marketing of Café@Lib.
Thesis (Bachelor of Library and Information Science)
Keywords: Coffee shops -- Philippines -- Quezon City; Public libraries -- Space utilization -- Philippines -- Quezon City